Farmer community participation in village building planning in Cikarawang Village, Bogor Regency - Ananda Bahri Prayudha; Lala M Kolopaking; Sofyan Sjaf (Jurnal Sosiologi Dialektika, 2022)
The stages of implementing Village Development Planning Deliberations are often carried out without involving the farming community so they have not been able to produce the formulation of development programs needed by farmers according to the mandate of Law no. 6 of 2014 concerning Villages, which contains the concept of village development as improving the quality of services, development, and empowerment of rural communities through a participatory approach. The purpose of this study was to determine the typology of farmers based on capital ownership and participation in planning and deliberation of village development planning, the typology of farming communities based on the type and capital ownership of community actors involved in the arena of village planning and development contestations planning meeting. This study uses the constructivism paradigm using qualitative methods with data collection techniques through observation, in-depth interviews, and focused discussions with a case study approach conducted in Cikarawang Village, Dramaga District, Bogor Regency. The result of this research is that the typology of farmers is divided into five types based on their capital ownership, namely Menlen, Biglen, Kolen, Renlen, and Nidlen types. The typology of farming communities in planning and musrenbangdes is passive, informative, functional, interactive and mobilization participation which is also influenced by ownership and capital accumulation.